Financial markets and the current account: emerging Europe versus emerging Asia - Sabine Herrmann; Adalbert Winkler (Deutsche Bundesbank, 2008)
Financial globalisation has been associated with divergent current account patterns in emerging market economies. While countries in emerging Asia have been running sizeable current account surpluses, countries in emerging Europe have been facing large current account deficits. In this paper we test for the relevance of financial market characteristics in explaining divergent current account patterns in emerging Europe and emerging Asia based on the assumption that both regions constitute two different convergence clubs with the euro area and the US representing the core, respectively. In line with the theoretical literature, we find that better developed and more integrated financial markets increase emerging markets ability to borrow abroad. The degree of financial integration within the convergence clubs as well as the extent of reserve accumulation are found to be the most significant factors to explain divergent current account patterns in emerging Europe and emerging Asia. We conclude that the overall character of integration matters for the pattern of current account developments in catching-up economies.
Keywords: O53; F21; F15; O52; O16; 330; real convergence; economic integration; saving and investment; current account developments; financial markets; emerging market economies; Finanzmarkt; Internationaler Finanzmarkt; Marktintegration; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Entwicklungskonvergenz; Aufstrebende Märkte; Vergleich; Osteuropa; Asien